Interpreting and knowledge mediation in the healthcare setting: What do we really mean by “accuracy”? - Major, George; Napier, Jemina (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This paper explores the concept of “accuracy” in the context of interpreter-mediated healthcare interaction by reporting on a study of simulated doctor-patient consultations involving professional Australian Sign Language (Auslan)/English interpreters. Wadensjö’s (1998) taxonomy of renditions is used to analyse the ways interpreters convey health information. Our data reveals that interpreters frequently produce reduced and expanded renditions that are not detrimental to the message or the interaction. There has previously been little discussion of how qualified interpreters make these decisions, and we suggest that achieving accuracy in the healthcare setting may be a more dynamic and context-dependent process than previously suggested. While the use of role-plays can on the one hand can be considered a delimiting factor (due to their artificial nature), they also allow a systematic comparison of different interpreters, thus providing more robust evidence for healthcare interpreter training.